Analisa Penurunan Susut Non Teknis Dengan AMR PLN (Studi Kasus PT. Tjokro Bersaudara Bontang Kaltim) - Abdur Rachman Tanjung; Abdul Zain; Herri Susanto (Jurnal Teknik Mesin Sinergi, 2019)
One of the problems faced by PLN is the high non-technical shrinkage of potential AMR customers due to installation and maintenance errors. This problem certainly has a solution that can be used so that non-technical losses can be suppressed. Based on the theory of electric energy calculation, from the voltage, current and power factor, it can be seen that the energy consumption is calculated or paid every month. Then done using the AMR application to monitor and analyze the use of electrical energy to potential customers with known data sources. Monitoring with this AMR application can make it easier to determine electrical energy deviations that have not been measured by the kWh meter, so as to accelerate normalization in case of errors or anomalies in the kWh meter. The results of the study explained that an abnormality was found due to the reverse polarity of the CT causing losses to the PLN which resulted in a subsequent bill of PT. Tjokro Bersaudara Bontang Kaltim Rp. 134,902,352.00.